SO017EFFECT OF HIGH-CUTOFF DIALYSIS FOR ACUTE KIDNEY INJURY SECONDARY TO CAST NEPHROPATHY IN PATIENTS WITH MULTIPLE MYELOMA: A SYSTEMATIC REVIEW AND META-ANALYSIS. (6th June 2020) - Tarragon, Blanca; Ye, Nan; Gallagher, Martin; Sen, Shaundeep; Portoles, Jose' M; Wang, Amanda
Abstract: Background and Aims: The incidence of multiple myeloma (MM) is increasing. Abnormal secretion of serum free light chains (sFLC) can lead to cast nephropathy and severe acute kidney injury (AKI) requiring haemodialysis (HD), which is associated with increased morbidity and mortality. High cut-off (HCO) HD membranes demonstrate better sFLC clearance. However, their role in all-cause mortality and renal recovery remains uncertain. Method: A systematic review and meta-analysis was performed examining all randomized controlled trials (RCTs) and observational studies assessing the effect of high cut-off HD compared to conventional HD on clinical outcomes of patients with MM complicated by cast nephropathy induced-severe AKI. Medline, EMBASE, and the Cochrane Central Register of Controlled Trials were searched until September 2019. The primary outcome was all-cause mortality at the end of the study. The secondary outcomes included all-cause mortality at 12 months, haemodialysis independence at 3, 6 and 12 months, biopsy-proven haematologic responses at 90 days and sFLC (kappa and lambda) reduction. Random effect models were used to pool relative risks (RR) with 95% conﬁdence intervals (CIs) for individual studies. Results: The search identified 5 studies including 276 patients with a mean follow-up of 18.7 months. There were 2 RCTs and 3 retrospective cohort studies. Compared with patients treated with conventional HD, patients on HCO dialysis did not show survival benefits at 12 months (4 studies, 186 patients, RR 0.79; 95% CI 0.46-1.36), or at the end of the study (5 studies, 276 patients, RR 0.86; 95% CI 0.60-1.25). Although survival benefits at the end of study (3 studies, 88 patients, RR 0.64; 95% CI 0.45-0.90) were seen in observational studies, no differences in all-cause mortality was seen in RCTs (2 studies, 188 patients, RR 1.31; 95% CI 0.50-3.46). Likewise, although the pooled data from the observational studies demonstrated significantly higher rates of HD independence at 90 days (2 trials, 78 patients, RR 2.23; 95% CI 1.09-4.55), this difference disappeared when the data from RCTs were included to the analysis (4 studies, 266 patients, RR 1.28; 95% CI 0.95-1.73).  There was no difference in HD Independence at 6 months (2 studies, 188 patients, RR 1.19; 95% CI 0.68-2.06), and 12 months (2 studies, 188 patients, RR 1.14; 95% CI 0.58-2.26) between these two therapies. Patients receiving HCO dialysis, however, had significantly better biopsy-proven haematologic response at 90 days by 40% (3 studies, 176 patients, RR 1, 40; 95% CI 1.13-1.74) and a significantly higher kappa light chain reduction (2 studies, 188 patients, standardized mean difference (SMD) 2.37; 95% CI 1.99-2.75; I2 = 0%). Overall, the majority of the studies were of suboptimal quality and underpowered. Conclusion: Current evidence from RCTs and observational studies suggest HCO dialysis provides haematological benefits but makes no significant improvement in all-cause mortality and renal outcomes, compared to conventional HD for patients with multiple myeloma associated cast nephropathy. However, there is a trend towards better renal outcomes, therefore further large-scale RCTs are needed to assess the effect of HCO dialysis on clinical outcomes in patients with multiple myeloma complicated by cast-nephropathy.